Assessing changes in choroidal vasculature in the eye in Down's syndrome: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Csincsik, Lajos; Nelson, Rachel; Walpert, Madeleine; Little, Julie‐Anne; Doyle, Lesley; Saunders, Kathryn; Peto, Tunde; Holland, Tony; Lengyel, Imre
Abstract: Background: Changes of choroidal vasculature in the eye have been reported in Alzheimer's disease (AD) and this is positively correlated with declining cognitive status. Patients with Down's syndrome (DS) are at a high risk of developing AD and also show signs of premature ageing. Both AD and ageing have been associated with thinner choroid, measured on optical coherence tomography (OCT) scans, however, there are currently no studies in the literature to evidence whether choroidal thinning occurs in DS. Our study, for the first time, investigated choroidal thickness (CT) in DS using OCT imaging. Method: 21 DS and 9 controls (Ctrl) were imaged using Enhanced Depth Imaging Spectral Domain OCT (Heidelberg). The choroid was manually segmented, and thickness values calculated using conventional grading grid (ETDRS). Statistical analysis was conducted in SPPS using only the right eye. The analysis was controlled for age, image quality, refractive error and time of the scan as covariates. Result: OCT imaging in DS proved to be challenging due to some participants having difficulties maintaining the fixation for an extended period. In this preliminary cohort the DS group was older than the Ctrl group (39.5±6.9 vs 31.2±6.0 years, p=.004) but there was no difference in gender (χ2=0.7, df=1, p=.376). Sub‐foveal (SF) and Superior‐inner (SI) CT was significantly increased in DS compared to Ctrl (SF: 363.2µm±25.9µm vs 237.3µm±45.8µm, p=.046; SI: 381.8µm±26.2µm vs 253.6µm±46.3µm, p=.044) but no differences were found in other sectors of the ETDRS grid. Increase in SF CT showed a moderate, positive correlation with cognitive status in the 14 participants whose cognitive score was available (ρ=.539, p=.047). Suprachoroidal space (SCS) as a hypo‐reflective band at the choroidal scleral interface, was only visible in DS in 13 (61.9%) out of the 21 participants. Those with SCS were older than those without (41.9±1.7 vs 35.6±2.2 years, p=.040). Conclusion: In this study we found that there is an increase in choroidal thickness in DS which is in contrast to the thinning observed in AD; this might be an anatomical feature of DS or may reflect inflammation. The increased prevalence of SCS in DS is likely to be associated with the accelerated ageing.